INFLATION FLUCTUATIONS AND ECONOMIC TURBOS IN INDONESIA - Ade Novalina; Dewi Mahrani Rangkuty; Jannatun Aswani (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to determine whether the money supply, investment, consumption, and economic growth variables have a significant effect on inflation. To find out whether the variables of government expenditure, unemployment, and inflation have a significant effect on economic growth. The data analysis model in this study is simultaneous regression. The data analysis technique used is the quantitative method. Data were processed from the Central Bureau of Statistics from 2007 to 2021. The results of this study indicate that based on the estimation results, the t-count value is obtained, the money supply variable has a significant effect on inflation. The investment variable has no significant effect on inflation. The consumption variable has no significant effect on inflation. The economic growth variable has no significant effect on inflation. The government expenditure variable has a significant effect on economic growth. The unemployment variable has a significant effect on economic growth. The inflation variable has a significant effect on economic growth. In order to reduce the inflation rate to a low level, Bank Indonesia should use monetary policy to reduce the money supply.